Excellence in management : practical applications for success - Conlow, Rick (Crisp Pub. Menlo ParkUS, 1991)
Presents skills and techniques of management that can produce workplace excellence. These include: setting clear goals with employees; confronting problems; listening effectively; creating superior customer service; managing time; hiring the best employees; and improving problem-solving skills.